Allelopathic Effect of Italian Cocklebur on Sugar Beet - Dávid, István; Radócz, László (Acta Agraria Debreceniensis, 2005)
Cockleburs are noxious weeds in Hungary, where they are widespread in row crops, especially in maize, sunflower and sugarbeet. A low density population of these weeds may be harmful because of their large competitive ability, fast growth in early phenological stages, allelopathy, and persistant sprouting.Allelopathy of Xanthium italicum Mor. was examined during the growing season in 2004. Root and shoot samples were collected at 4 or 5 leaves stage (in the end of May and in the beginning of June) and before flowering (in the beginning of July) before and after rain. Extracts were made in tap water. The test plant was Beta vulgaris L.; its germination, root and shoot growth were evaluated at the 6th and 10th days after treatment.Most of extracts inhibited the germination of sugar beet. In these experiments the phenological stage of the donor plant determined slightly the effectiveness of the extracts on sugar beet. Generally, significant differences existed between treatments only in cases of concentrated extracts.Rainfall can modify the inhibitory effect of extracts (especially shoot extracts). Shoot extracts of young plants inhibited stronger germination and growth after rain than before rain. Density of cockleburs influenced the effect of extracts, as well. Generally, differences between the efficacy of extracts was larger after rain.The results supported the hypothesis that the phenological stage and some environmental factors can modify allelopathy of cockleburs.